Larval morphology and analysis of primary chaetotaxy in the genus Suphis Aubé, 1836 (Coleoptera: Noteridae) - Urcola, Juan I.; Alarie, Yves; Benetti, Cesar J.; Rodriguez, Georgina; Michat, Mariano C. (Zootaxa, 2019)
The three larval instars of Suphis cimicoides Aubé, 1837 are described and illustrated, including morphometric and chaetotaxic analyses of the cephalic capsule, head appendages, legs, last abdominal segment and urogomphus. A preliminary ground plan of primary chaetotaxy for noterid larvae is presented for the first time, based on the species described herein and examination of larvae of the genera Hydrocanthus Say, 1823 and Suphisellus Crotch, 1873. This ground plan is compared with previous systems proposed for other adephagan families. Larvae of Noteridae can be distinguished from those of other families of Hydradephaga by the following combination of characters: (1) antennomere 3 with a rugged area on distal portion; (2) abdominal segment VIII with a U-shaped wavy membranous area ventrally; (3) absence of pore FRd; and (4) presence of seta AB16. Several sensilla present in noterid larvae (notably setae TR2 and TA1 and pores PAl, PAm, COd, TRb and FEb) are absent in larvae of Meruidae. On the contrary, parietal seta PA5 is present in Meruidae but absent in Noteridae. The presence of pore COc in Noteridae may indicate that this family has retained the ancestral condition found only in Carabidae. On the other hand, the absence of setae FE7, FE8, FE9 and FE10 in Noteridae is similar to the condition found in Carabidae, Gyrinidae and Meruidae.